Comparative Analysis of Certain Morphological Characteristics of Top Tennis Players in Different Periods - Jovanka Mimic; Veljko Vukicevic; Nadja Vujacic (Journal of Anthropology of Sport and Physical Education)
An interdisciplinary approach to solving the issue of professional tennis playing is all the more becoming a condition for further development and planning regarding the sport. The aim of this study is to determine statistically relevant diff erences among top tennis players over the various periods expressed in the measures used for assessing morphological characteristics. A survey has been conducted with the objective of putting a bigger focus on the selection of tennis players based on body height, body mass, BMI and the age in various periods of tennis playing. The sample of respondents consisted of 50 tennis players for a period of 40 years. Data were taken regarding 10 most successful tennis players for the respective year on the account of their ATP ranking. The results derived from the univariate analysis of variance indicated that the examinees from various periods of playing tennis diff erentiated among each other with respect to body mass, nutrition state and years of age. Examinees from a group of tennis players active in 1986, on average had better and statistically more relevant BMI values when compared to the examinees from the 2006 group and 2016 group. Moreover, it was noted that the examinees from 1986 were statistically younger in relation to the examinees from 2016. It can be assumed that for successful tennis playing in the last decade certain experience is required, as well as age, including body mass which needs to be slightly bigger, but to the advantage of muscle mass.